Influence of anti-epileptic drugs on hematological and biochemical parameters in patients with epilepsy - Dwajani, S.; Ranjana, G.; Sarma, G. R. K.; Kulkarni, Chanda; Ganapathi, B. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Epilepsy is a chronic neurological condition which may require long-term treatment with antiepileptic drugs (AEDs). The challenge in AED management is to attain freedom from seizures, without side-effects and with good quality-of-life. However, AEDs are reported to induce potential adverse effects, which can remain unnoticed over long time. In this regard, earlier studies report inconsistent results in hematological and biochemical toxicity of AEDs. The objective of the present study was to evaluate the effects of AED monotherapy and polytherapy on hematological and biochemical parameters. Methods: This was a cross-sectional, observational study carried out among patients with epilepsy (PWE) receiving AEDs. The data on baseline demographic characteristics, treatment, adverse drug reactions, hematological, and biochemical investigations were collected. Statistical analysis was performed using the SPSS version 18 and descriptive statistics such as mean and median were used to summarize the data and inferential tests like Chi-square was used to compare categorical variables between groups. Results: There were 255 PWE in mean age range of 28.68±9.29 years, with 56.54% males. A total of 78.04% had focal, 18.04% had generalized seizures and remaining 3.92% were unclassified. Majority of (55.69%) PWE received polytherapy with AEDs. Females had significantly lower levels of hemoglobin (Hb) when compared with males (p=0.000), and patients on AED polytherapy showed significant difference in low Hb (p=0.006) and high alkaline phosphatase (ALP) levels (p=0.001). Conclusions: The results of this study showed significant alterations in the levels of Hb and ALP with the use of AED polytherapy in PWE. Routine hematological and biochemical investigations may be considered during AED treatment in those patients receiving AED polytherapy.